The prognostic significance of neuroendocrine markers and somatostatin receptor 2 in hepatocellular carcinoma. Issue 10 (28th July 2021) - Murakami, Keigo; Kumata, Hiroyuki; Miyagi, Shigehito; Kamei, Takashi; Sasano, Hironobu
Abstract: Prostatic and colon carcinomas with neuroendocrine differentiation are reported to behave more aggressively than those without such differentiation. In hepatocellular carcinomas (HCCs), however, only a few studies have reported the expression status of neuroendocrine markers and somatostatin receptor 2, the main target of a somatostatin analog. Furthermore, the prognostic significance of the markers in HCCs has not been fully explored. We evaluated the expression of the neuroendocrine makers (chromogranin A, synaptophysin, and CD56) and somatostatin receptor 2 (SSTR2) in 95 HCCs, and investigated the correlation between the expression of these markers and clinicopathological findings. Chromogranin A was immunolocalized in 2 cases, synaptophysin in 15 cases, CD56 in 11 cases, and SSTR2 in 19 cases. Immunoreactivity of synaptophysin and CD56 were the significant unfavorable prognostic factors in terms of 2‐year disease‐free survival (DFS) and the overall survival (OS) along with a high nuclear mitosis level (>10/10 high‐power field), a larger tumor size (>5 cm), the presence of vascular and/or biliary invasion, and high TNM stage (III/IV). Multivariate Cox proportional hazards analysis identified synaptophysin as an independent prognostic factor for 2‐year DFS and OS. Synaptophysin expression can be used to predict an unfavorable prognosis in patients with HCC.